2015
DOI: 10.1103/physrevlett.114.013201
|View full text |Cite
|
Sign up to set email alerts
|

Body-Assisted van der Waals Interaction between Excited Atoms

Abstract: We present a formula for the body-assisted van der Waals interaction potential between two atoms, one or both being prepared in an excited energy eigenstate. The presence of an arbitrary arrangement for a material environment is taken into account via the Green function. The resulting formula supports one of two conflicting findings recorded. The consistency of our formula is investigated by applying it for the case of two atoms in free space and comparing the resulting expression with the one found from the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…ω) corresponding to the contributions from the free space and the reflection by graphene, respectively. The free space Green tensor has been analytically given in [46][47][48]. The reflection Green tensor can be obtained from the optical conductivity of a graphene layer (see more details in appendix E).…”
Section: Near-field Enhancement Of the Entanglement Forcementioning
confidence: 99%
“…ω) corresponding to the contributions from the free space and the reflection by graphene, respectively. The free space Green tensor has been analytically given in [46][47][48]. The reflection Green tensor can be obtained from the optical conductivity of a graphene layer (see more details in appendix E).…”
Section: Near-field Enhancement Of the Entanglement Forcementioning
confidence: 99%
“…If one of the emitters is not in its fundamental electronic state, the potential changes as a result of Förster-like processes [17,[25][26][27][28][29][30],…”
Section: Observable Far-field Potentialsmentioning
confidence: 99%
“…For nS-1S interactions (atomic hydrogen), this problem has recently been investigated in [3]. It was found that the interesting oscillatory 1/R 2 long-range tails [4][5][6][7][8][9][10] are numerically suppressed and become dominant only for excessively large interatomic distances, in a region where the absolute magnitude of the interaction terms is numerically insignificant. Indeed, the Casimir-Polder regime of a 1/R 7 interaction is never reached for systems with at least one atom in an excited state [9,10].…”
Section: Introductionmentioning
confidence: 99%